2011
DOI: 10.1088/0004-637x/743/1/50
|View full text |Cite
|
Sign up to set email alerts
|

THE DISCOVERY OF Y DWARFS USING DATA FROM THEWIDE-FIELD INFRARED SURVEY EXPLORER(WISE)

Abstract: We present the discovery of seven ultracool brown dwarfs identified with the Wide-field Infrared Survey Explorer (WISE). Near-infrared spectroscopy reveals deep absorption bands of H 2 O and CH 4 that indicate all seven of the brown dwarfs have spectral types later than UGPS J072227.51−054031.2, the latest type T dwarf currently known. The spectrum of WISEP J182831.08+265037.8 is distinct in that the heights of the J-and H-band peaks are approximately equal in units of f λ , so we identify it as the archetypal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
475
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(496 citation statements)
references
References 59 publications
20
475
1
Order By: Relevance
“…HR 8799b, HD 189733b; Barman et al 2011;Sing et al 2009Sing et al , 2011. The recently discovered Y dwarfs (Cushing et al 2011) approach the temperature of Jupiter. Since brown dwarfs never achieve a stable nuclear burning phase, they cool throughout their lifetimes, and temperature, rather than mass, is the dominant factor in defining the spectral sequence.…”
Section: Introductionmentioning
confidence: 95%
“…HR 8799b, HD 189733b; Barman et al 2011;Sing et al 2009Sing et al , 2011. The recently discovered Y dwarfs (Cushing et al 2011) approach the temperature of Jupiter. Since brown dwarfs never achieve a stable nuclear burning phase, they cool throughout their lifetimes, and temperature, rather than mass, is the dominant factor in defining the spectral sequence.…”
Section: Introductionmentioning
confidence: 95%
“…Objects transitioning from L to T spectral types undergo a dramatic shift to bluer near-IR colors, thought to be driven by the clearing of clouds and the formation of methane (e.g., Burgasser et al 2002;Chiu et al 2006;Saumon & Marley 2008). UKIDSS and WISEhave illustrated the diversity of late-T and Y dwarf near-and mid-IR colors (e.g., Burningham et al 2010b;Kirkpatrick et al 2011;Mace et al 2013), and WISEhas enabled the discovery of the coolest known substellar objects (e.g., Cushing et al 2011;Kirkpatrick et al 2012;. Large samples have revealed the mass and luminosity functions of the local ultracool population (e.g., Allen et al 2005;Cruz et al 2007;Burningham et al 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Lucas et al (2010) reported the discovery of an even cooler object UGPS 0722−05 which they suggested should be classified as T10, and could in the future be regarded as the first example of a new spectral type. In 2011, Cushing et al (2011) reported the 'Discovery of Y-dwarfs'. Several objects identified using the WISE satellite were found to be of later spectral types than UGPS 0722−05.…”
Section: Y Dwarfsmentioning
confidence: 99%